PENERAPAN METODE DEEP LEARNING UNTUK OTOMATISASI PENILAIAN ESAI BERBAHASA INDONESIA - Sri Rezki Maulina Azmi; Dewi Anggeraini (Smart Education, 2026)
Indonesian language instruction within tertiary educational institutions in Indonesia encounters a significant hurdle due to students' inadequate literacy capabilities. A potential method to address this issue is the integration of deep learning techniques to enhance language proficiency. This research This research is designed to investigate the implementation of deep learning in the acquisition of the Indonesian language, emphasizing aspects such as historical analysis of the language, spelling verification (EYD), selection of words (diction), arrangement of paragraphs, and scientific writing conventions. The approach employed is a Systematic Literature Review (SLR), aiming to pinpoint and compile existing research pertinent to the use of deep learning in educational settings. Findings indicate that utilizing deep learning can serve as an effective strategy for boosting students' comprehension of the rules governing the Indonesian language through automated feedback that aids in refining spelling, sentence construction, and vocabulary selection. This methodology not only expedites the educational process but also elevates the quality of writing while facilitating the enhancement of students' skills in scientific writing. Deep learning offers a more engaging and relevant framework for studying the Indonesian language at the university level.